Analysis of metabolomics associated with quality differences between room‐temperature‐ and low‐temperature‐stored litchi pulps. Issue 11 (30th September 2019) - Guo, Xiaomeng; Luo, Tao; Han, Dongmei; Wu, Zhenxian
Abstract: Studies on how temperature affects the postharvest quality of litchi have focused mainly on pericarp browning but rarely on the metabolites in postharvest litchi pulp. In this study, the differences in respiration rates, total soluble solid content, and titratable acid content demonstrated that room and low temperatures have different effects on the quality of "Feizixiao" litchi pulp. UHPLC‐ESI‐QTOF‐MS/MS analysis was performed to compare the differentially expressed metabolites (DEMs) in litchi pulp after 8 days of storage at room temperature (RT‐8 d) with those in litchi pulp after 28 days of storage at low temperature (LT‐28 d). Nineteen carbohydrates (phosphohexoses, sorbitol, and mannose), fifteen acids, seven amino acids, nine energy metabolites and nucleotides, and six aliphatic and secondary metabolites were identified as common DEMs in RT‐8 d and LT‐28 d pulps. These findings indicated active fructose and mannose metabolism and increased catabolism of nicotinate, nicotinamide, alanine, aspartate, and glutamate. Four carbohydrates (mainly phosphohexoses), five acids, ten amino acids, three aliphatic and secondary metabolites, and one hormone were identified as unique DEMs in RT‐8 d pulp, the consumption of key metabolites in glycolysis and the tricarboxylic acid cycle, and accumulation of phenylalanine, tyrosine, and tryptophan. Active consumption of nucleotide metabolites and biosynthesis of aliphatics in LT‐28 d pulp were indicated by unique DEMs (eleven carbohydrates, four acids, seven amino acids, seven energy metabolites and nucleotides, and six aliphatic and secondary metabolites). These results provided an unambiguous metabolic fingerprint, thereby revealing how room and low temperatures differentially influenced the quality of litchi pulp. Abstract : This study definitely provides a metabolic fingerprint that reveals the different effects of room‐temperature and low‐temperature storage on the physiological activities and quality of litchi pulp.